Use of vascular clips to approximate skin grafts on the burned hand - Rachael M. Payne; Luis Quiroga; Carisa M. Cooney; Julie A. Caffrey (Elsevier, 2018)
Background: Burns of the hands are common and can lead to significant functional and aesthetic impairment. Traditionally, sutures or staples are used to approximate adjacent skin grafts on the hand; however, we have found that vascular clips are a suitable alternative. We report a series of three patients in which vascular clips were used to approximate adjacent skin grafts autografted to treat full-thickness burns. Methods: Three patients presented with full-thickness burns involving their hands. Vascular clips were used to adhere adjacent skin grafts to the dorsal surfaces of the hands. Two patients sustained bilateral burns to the hands; vascular clips were used on one hand while sutures or staples were used on the other hand. In another patient, vascular clips were used. Results: Satisfactory functional and aesthetic outcomes were observed in all three patients 1-2 months post-reconstruction. One patient had hypertrophic scarring at multiple graft sites including his hands. Similar functional and aesthetic outcomes were achieved in both hands of the patients who had skin grafts approximated with vascular clips and traditional methods. Conclusion: Use of vascular clips to approximate skin grafts on the hands is a simple and effective method resulting in satisfactory functional and aesthetic outcomes. Keywords: Skin graft, Vascular clip